Alternative financing opportunities in the public sector. Theoretical overview and the example of the Hungarian „Diákhitel II.” (Student loan 2) - Balogh, László; Balogh, Máté; Ágoston, Anita (Acta Scientiarum Socialium, 2013)
Alternative financing opportunities in the public sector. Theoretical overview and the example of the Hungarian „Diákhitel II.” (Student loan 2). To the state with the problems of national debt, the pressure of economic recovery and transportation costs, the question of how to manage during the allocation without damaging the fundamental social goals and interests (harm minimization) is even more urgent. In connection with this problem we summarized the results up to now of our research about the growth of public expenditure in the 20th century. We briefly touch the literatures’ results on stopping the expenditures and finally we reveal some problem and opportunity of searching financing alternatives with the help of the Hungarian „Diákhitel II” (Student Loan 2) construction.
Keywords: role of the state; public expenditure; alternative financing; student loan